Green Innovation on the Business Performance of Halal-Certified Micro, Small, and Medium Enterprises in South Sulawesi - Ridwan, Hardiyanti; H. Kara, Muslimin; Wahab, Abdul; Ayu Parmitasari, Rika Dwi; Nabir, Abd. Muhaemin; Nurwahida, Nurwahida (International Journal of Management Science and Information Technology, 2025)
This study aims to analyse the effect of green innovation on the business performance of micro and small enterprises in South Sulawesi, particularly those that have obtained halal certification. Green innovation is a new strategy that has emerged among business actors, involving the creation of environmentally friendly innovations in the production process and the products produced. The research method used is explanatory research with a quantitative approach, with a population of 1,025 MSEs and a sample of 124 MSEs with halal certification. The data collection techniques used were observation, interviews and questionnaires with a 1-7 Likert scale, while the data analysis techniques used were descriptive statistical analysis and inferential analysis, namely inner model and outer model analysis, as well as hypothesis testing. The results of the study indicate that green innovation has a positive and significant effect on the business performance of micro and small enterprises in South Sulawesi -, amounting to 45.1%. This implies that the implementation of green innovation in SMEs that already have halal certification can improve business performance while promoting economic, social, and environmental sustainability.